Avaliação de iniciativas para gestão de resíduos sólidos urbanos nos municípios integrantes do Consórcio Intermunicipal do Oeste Paulista (CIRSOP) - Pestana, Laura de Oliveira Battistini (2023)
The increase in the population's consumption rates, domestic activities and sweeping and public cleaning services results in the generation of municipal solid waste (MSW). When disposed of inadequately, they generate negative impacts, capable of causing interference to human health and the environment. In 2010, the Federal Law 12,305/2010 established the National Policy for Solid Waste (NPSW), responsible for regulating aspects involving the integrated management of solid waste. Its text highlights guidelines and initiatives to ensure that its objectives are met, 5 of which are the object of this research: sanitary landfill, selective collection, composting, reverse logistics, and public consortium. The latter allows for regionalized arrangements of service provision and greater concentration of resources to enable the implementation of the other guidelines foreseen in the legislation. The objective of the study was to evaluate the implementation of the NPSW initiatives for the municipalities of the Intermunicipal Consortium for Solid Waste Management of Western São Paulo (CIRSOP). The methodology consists of 6 steps, which are: i) Identification of studies on NPSW recommendations; ii) Characterization of the study object; iii) Evaluation of the guidelines by the SAGReS software; iv) Preparation of georeferenced maps; v) Recommendations for CIRSOP; vi) Comparative analysis between the research results and the proposals of the consortium's Intermunicipal Plan for Integrated Solid Waste Management. The results show that NPSW initiatives are not widely applied in the studied consortium municipalities. Of the total of 10 municipalities, 50% send their solid waste to sanitary landfills. Furthermore, there is: i) lack of control of working conditions in the selective collection cooperatives, ii) lack of environmentally adequate final destination of organic waste through composting, iii) lack of control of parameters for reverse logistics and, finally, iv) the need to disseminate information online, as these are not fully available and/or updated. Among the recommendations for the CIRSOP, there are activities focused on environmental education, implementation of shared sanitary landfills, control of management operations through indicators and encouragement of domestic composting stand out.